2022
DOI: 10.1088/1612-202x/ac4915
|View full text |Cite
|
Sign up to set email alerts
|

Orbital angular momentum induced bistability in a quantum system

Abstract: In this article, we have proposed a unique approach to adjust optical bistability (OB) and optical multistability (OM) in a ring cavity inclusive of a three-level quantum system primarily based on quantum mean-field theory. The quantum system interacts with a weak probe light, an incoherent pumping field and a robust coupling light which carries an optical vortex that is an electromagnetic light with optical angular momentum. We confirmed that the real and imaginary parts of the susceptibility of the no-vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A pivotal requirement is the interaction between a light source and a material, which can span across diverse mediums [13][14][15][16][17][18][19]. When an atom engages with a field, the resulting atomic coherence emerges as a crucial mechanism, facilitating effective control and modulation of the optical properties within quantum systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A pivotal requirement is the interaction between a light source and a material, which can span across diverse mediums [13][14][15][16][17][18][19]. When an atom engages with a field, the resulting atomic coherence emerges as a crucial mechanism, facilitating effective control and modulation of the optical properties within quantum systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…primarily based on quantum interference phenomena and atomic coherence [5][6][7]. The foundations of quantum coherence and interference extend to atom-field interactions [8][9][10][11], measurement theory [12], enormous Kerr nonlinearities [13], and many other areas of atomic physics and quantum optics [14][15][16][17]. For quantum interference-based 1D atom grating, several different techniques have been presented [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…EIT has found extensive use in the study of light-matter interactions, owing to its noteworthy quantum coherent properties [2][3][4][5][6][7]. EIT is particularly relevant for diverse applications, including slow light [8][9][10], the creation of a significant nonlinear response [11,12], the generation of an electromagnetically induced grating (EIG) [13][14][15][16][17][18] and other related phenomena [5,[19][20][21][22][23][24][25]. Recent studies have observed the EIG phenomenon in atomic systems, quantum wells, and quantum dots [26][27][28].…”
Section: Introductionmentioning
confidence: 99%